Analysis Of the Effectiveness of LKPD Based on Project Based Learning (PJBL) To Stimulate Students’ Critical Thinking - Kris Dayanti; Nanang Khuzaini; Bernard Febriyanto; Syahrul Gunadi; Nady Fricelaa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
Critical thinking skills master the material where students know, know, master, and are able to express concepts in a form that is more accessible. However, critical thinking skills still tend to be low. So it takes teaching materials that integrate these abilities. For this reason, this study aims to develop Student Worksheets (LKPD) based on Project Based Learning (PjBL) in the context of critical thinking for class VII students on quality triangles and quadrilaterals seen from aspects of validity, practicality and effectiveness. This type of research is descriptive qualitative. This research was conducted in one of the junior high schools in Yogyakarta. The subjects in this study were 32 students of class VIIC. Data collection techniques used interviews, concept understanding ability tests, and preliminary questionnaire studies. While the data analysis technique uses the Miles and Huberman model which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the teacher has carried out learning assisted by LKPD teaching materials. Based on the results of the assessment of material experts and media experts, the learning media is feasible to use with improvements. The assessment by the material expert obtained a score of 161 and converted into the “Good (B)” category and the results of the assessment from the media expert obtained a total score of 59 with the “Good (B)” category so that the learning has met the validity aspect, (4) Trial limited research involving 6 students, (5) Extensive Product Test was carried out on 32 grade VII students of SMP Negeri 12 Yogyakarta and the results of the student response questionnaire obtained a total score of 1504 with the category “Very Good (SB)” and has fulfilled the practicality aspect, (7) Revised Wider Field Test Results. From the results of the pre-test and post-test the average pre-test score was 24.38 and the post-test average score was 82.25 and the calculation results were in the “High” category and had fulfilled the effectiveness aspect.